Globalizing Rural Egypt: Women, Men, and the Agrarian Division of Labor - James Toth (Revue des Mondes Musulmans et de la Méditerranée)
It is tempting to see globalization as a response to large, impersonal market forces detached from individual agents and their more parochial interests. Yet while such abstract forces might set up appealing conditions, motivations and intentions operate at a more concrete level. This example from Egypt demonstrates that a near-constant “battle of the sexes” in rural Egypt, perpetrated by patriarchal stereotypes and wage differentials, provides a critical dynamic that feeds both the rural and urban labor markets in one politically important “node” of the expanding global economy. After drawing the formal contours of this “battle”, this chapter first examines the cataclysmic agricultural crisis of 1961 that is best explained by recourse to gender inequities. It then demonstrates how more recently, workers of both genders have resisted these gender wars, stereotypes, and inequalities and, in the process, have established more formal, now religious, opposition to Egypt’s dismal position in the global division of labor.